DNA Damage in Lymphocytes in Hypertensive Subjects in Bangladesh (Journal of Scientific Research, 2013)
Oxidative stress due to imbalance between the production of reactive oxygen species and their dismutation is claimed to be higher in hypertensive subjects than normotensive subjects. In hypertensive subjects oxidative stress may damage deoxy-ribonucleic acids (DNA). In this study plasma superoxide dismutase (SOD) activities, protein carbonyl contents (PCCs) and extent of DNA damage in lymphocytes were measured in specimens obtained from 86 subjects to compare oxidative stress and oxidative DNA damage between normotensive and hypertensive subjects and to assess their relationship with the degree of blood pressure. Results were expressed as mean±SD. Two-tailed unpaired t test and Pearsons correlation test were done to compare or to determine the relationship between groups or variables. SOD activities were 2.85±0.12 unit/mg protein and 3.84±0.45 unit/mg protein (p